2010
DOI: 10.4137/bmi.s5305
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Homocysteine and C-Reactive Protein in the Saliva of Healthy Adults: Comparison with Blood Levels

Abstract: Inflammation and cardiovascular disease are associated with elevated serum levels of C-Reactive Protein (CRP) and homocysteine. The presence of both molecules in saliva provides an opportunity for development of non-invasive assessments of disease risk. However, salivary CRP and homocysteine reference ranges and their correlation with serum levels are unknown. This study investigated if CRP and homocysteine could be routinely detected in the saliva of healthy adults and the relationship between salivary and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 16 publications
4
63
3
Order By: Relevance
“…A local synthesis in oral cavity of transferrin, alpha 1-acid glycoprotein, alpha 1-antitrypsin and haptoglobin was observed in infants (Szabo, 1988). Increased CRP mRNA expression in the submandibular glands of rats with experimentally induced inflammation was recently reported (Dillon, 2010). It is now widely accepted that acute phase protein synthesis may take place in extra-hepatic cell types.…”
Section: Origin Of Acute Phase Proteins In Salivamentioning
confidence: 93%
“…A local synthesis in oral cavity of transferrin, alpha 1-acid glycoprotein, alpha 1-antitrypsin and haptoglobin was observed in infants (Szabo, 1988). Increased CRP mRNA expression in the submandibular glands of rats with experimentally induced inflammation was recently reported (Dillon, 2010). It is now widely accepted that acute phase protein synthesis may take place in extra-hepatic cell types.…”
Section: Origin Of Acute Phase Proteins In Salivamentioning
confidence: 93%
“…The presence of C-reactive protein (CRP) molecules in saliva provides an opportunity for development of non-invasive assessments of cardiovascular diseases risk factors [67]. The use of this simple no invasive sample requires the establishment of salivary CRP reference ranges and their correlation with serum concentrations, which have not been investigated in detail yet.…”
Section: Future Of Metabolomics Biomarkers In Forensicsmentioning
confidence: 99%
“…7 Salivary CRP levels have been used to assess whether CRP determination in saliva samples could be utilized as a way to detect inflammation, and as an alternative approach to evaluate disease risk and monitoring the response to treatment. 8 Previous studies demonstrated that the plasma levels of hs-CRP are significantly decreased after exercise training program, 3,[9][10][11][12] suggesting that rehabilitation program may develop an anti-inflammatory reaction. However, reports showing the levels of hs-CRP in saliva before, during and after cardiac rehabilitation are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are produced in the salivary glands. 8 Since, a strong correlation between serum and nonstimulated salivary hs-CRP concentrations was observed before and after intervention, serum origin of hs-CRP is accepted. The association between serum concentrations of hs-CRP and stimulated saliva was not statistically significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation